A study of middle-class Singaporeans' identities and aspirations in the workplace - Toh, Josephine Hui Shan (2016)
This research aims to examine the processes involved in class identity negotiation among middle class Singaporeans and understand their perceptions of social mobility in this fast-paced and competitive society. Adopting the ‘culturalist’ approach to class analysis, this paper will then analyze how class operates through the individual working experiences of middle class Singaporeans. From the results, class identities are no longer required to be formed in a definite and obvious manner. Instead, class is embedded, lived and reproduced in an implicit and individualized manner, through the respective day-to-day working lives of the Singaporeans. The strategies they adopt to negotiate their middle class identities will be discussed in depth in this paper.